In what format and under what timeframe would China take on climate commitments? A roadmap to 2050 - ZhongXiang Zhang (Fondazione Eni Enrico Mattei (FEEM), 2010)
In what format and under what timeframe China would take on climate commitments is of significant relevance to China because it is facing great pressure both inside and outside international climate negotiations to exhibit greater ambition and is being confronted with the threats of trade measures. It is of significant global relevance as well because when China's emissions peak is crucial to determine when global emissions would peak and because what China is going to do in what format has significant implications for the level and ambition of commitments from other countries. In response to these concerns and to put China in a positive position, this paper maps out the roadmap for China's specific climate commitments towards 2050. Taking many factors into consideration, the paper argues that China needs to take on absolute emissions caps around 2030. While this date is later than the time frame that the U.S. and other industrialized countries would like to see, it would probably still be too soon from China's perspective. However, it is hard to imagine how China could apply the brakes so sharply as to switch from rapid emissions growth to immediate emissions cuts, without passing through several intermediate phases. To that end, the paper envisions that China needs the following three transitional periods of increasing climate obligations before taking on absolute emissions caps that will lead to the global convergence of per capita emissions by 2050: First, further credible energy-conservation commitments starting 2013 and aimed at cutting China's carbon intensity by 45-50% by 2020; second, voluntary 'no lose' emission targets starting 2018; and third, binding carbon intensity targets as its international commitment starting 2023. Overall, this proposal is a balanced reflection of respecting China's rights to grow and recognizing China's growing responsibility for increasing greenhouse gas emissions as China is approaching the world's largest economy.
Keywords: Q42; Q48; Q52; Q54; Q58; 330; Carbon Intensity Target; Binding Emissions Caps; Post-Copenhagen Climate Negotiations; Energy Saving; Renewable Energy; Clean Development Mechanism; China; USA; India